2017
DOI: 10.1080/17474124.2017.1284586
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal chemotherapy and cytoreductive surgery for peritoneal metastases coupled with curative treatment of colorectal liver metastases: an updated systematic review

Abstract: We aimed to assess the efficacy and safety of delivering intraperitoneal chemotherapy and cytoreductive surgery for peritoneal metastases coupled with curative treatment of colorectal liver metastases. Areas covered: A comprehensive literature search using PubMed was conducted to screen for eligible records. Studies evaluating colorectal surgery and intraperitoneal chemotherapy combined with curative treatment of liver metastases were included. We excluded duplicate publications. Sixty-seven full-text papers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
0
14
1
Order By: Relevance
“…Since Elias et al published the first report about combined resection with intraperitoneal chemotherapy for patients with peritoneal and liver metastases, several surgeons have tried to attempt this challenging surgical treatment [17]. A recently published systematic review showed that combined curative resection with intraperitoneal chemotherapy for peritoneal and liver metastatic CRC resulted in a possible survival benefit in selected patients [18]. However, there have been only a few studies regarding this treatment, therefore the feasibility and the efficacy is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Since Elias et al published the first report about combined resection with intraperitoneal chemotherapy for patients with peritoneal and liver metastases, several surgeons have tried to attempt this challenging surgical treatment [17]. A recently published systematic review showed that combined curative resection with intraperitoneal chemotherapy for peritoneal and liver metastatic CRC resulted in a possible survival benefit in selected patients [18]. However, there have been only a few studies regarding this treatment, therefore the feasibility and the efficacy is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, several publications have suggested the feasibility and shown the survival improvement of liver metastases resection without adding morbidity[50,51]. There is no consensus on the number of liver metastases that limits the indication for CRS plus HIPEC as long as complete resection can be fulfilled[52].…”
Section: Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemomentioning
confidence: 99%
“…In these patients, a recently updated review of clinically heterogeneous studies revealed a median overall survival that ranged from 6 to 49 months, which was lower than in patients with isolated PM in most of the included studies 55. Additionally, a recent meta-analysis reported a significantly higher risk of death (hazard ratio 1.30) for patients with both liver metastases and PM treated with curative intent compared to patients with isolated PM 56.…”
Section: Liver Metastasesmentioning
confidence: 97%
“…However, a curative approach may be considered in highly selected PM patients with limited and resectable hepatic disease 55,56. Consequently, over the last decade, a substantial number of studies have reported on patients who were treated with CRS and HIPEC combined with local treatment of liver metastases.…”
Section: Liver Metastasesmentioning
confidence: 99%